Daughters of Development: Women and Thailand’s Changing Environment - Sittirak, Sinith (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Although Thai women have no significant participation in the conception and implementation of ill-fitting development policies, they are nonetheless suspected of destroying Thailand's forests, poisoning its air and water and, in general, facilitating ecological degradation. Already powerless in a patriarchal society, women are expected to be knowledgeable of the most "environment-friendly" waste management techniques in the performance of domestic roles. While there have been notable instances where Thai women successfully prevented government programs from inflicting further damage to their lives and the environment, they continue to be the recipient of misplaced blame.